The Impact of Social Work Students’ Experience with Supervision - Karla Pobucká; Věra Malík Holasová; Veronika Mia Racko; Lenka Honsárková (Journal of Social Work Education and Practice)
The study intends to describe and explore the quality of the implementation of supervision training at the Faculty of Social Studies, University of Ostrava. Among other things, the study provides a brief insight into the concept of courses focused on supervision in social work at selected public universities and colleges in Czechia. Data are processed through evaluation research. The data were collected using four selected techniques: a focus group, an anonymous online questionnaire from class evaluations, an anonymous online questionnaire from full semester course evaluations, and students’ reflective journals. Data were collected continuously over the academic years 2020 to 2023. The total number of communication partners was n=80. The research was viewed through a qualitative research survey lens. The study findings confirm the specifics of educational supervision, where dilemmas arise between voluntary participation in a supervision class and the student’s mandatory completion of the course and between the teacher and supervisor roles. The actual type and form of study (Bachelor’s, Master’s, part-time, full-time) influences the supervision process. Students’ reflection skills and working with them are essential here. Still, they are influenced by the educational context (compulsory participation in a supervision class, little choice of groups and supervisor) and related ethical aspects. The social work educator must deal with these difficulties by, for example, involving learners in the evaluation and development of teaching, using various forms of supervision, and approaching teaching quality as a priority.